AB1346 PATIENTS' BELIEFS ABOUT MEDICINES PRESCRIBED FOR THEIR RHEUMATOID ARTHRITIS OR SPONDYLOARTHRITIS. (June 2019) - Madeira, Nathalie; Silva, Candida; Miguel, Claudia; Medeiros, Dina; Barcelos, Filipe; Santos, Helena; Trinca, Ricardo; Cardoso, Alexandra; Miranda, Luís Cunha
Abstract : Background: Adherence to therapies is determined by multiple factors, some of which are patient's related and include economic resources, knowledge, attitudes, beliefs, perceptions and expectations about medication. Objectives: To assess patients' beliefs about prescribed medication for their rheumatic disease (rheumatoid arthritis (RA) or spondyloarthritis (SpA), including psoriatic arthritis) and to determine the existence of any association between these beliefs and clinical and socio-demographic variables. Methods: Observational cross-sectional study which included RA patients according to 1987 ACR and/or 2010 ACR/EULAR criteria and SpA patients according to 2009 ASAS classification criteria (CC) for axial SpA or to 2011 ASAS CC for peripheral SpA, on subcutaneous biological therapy, followed at our Center, able to complete questionnaires autonomously and who agreed to participate. Socio-demographic and clinical data, anxiety and depression through the Hospital Anxiety and Depression Scale (HADS) and fatigue using the Functional Assessment of Chronic Illness Therapy - Fatigue questionnaire (FACIT-F) were collected. To assess beliefs about medication, the cross-culturally adapted Portuguese version of the Beliefs about Medicines Questionnaire (BMQ)-Specific was used, asking patients to apply it considering only the prescribed medicines for AR or SpA. The BMQ-Specific comprises two subscales: a five-item Necessity scale (Specific-Necessity, SN) and a six-item Concerns scale (Specific-Concerns, SC). Each item is scored on a five-point Likert scale (from 1 = strongly disagree to 5 = strongly agree). Statistics: descriptive, Mann-Whitney and Kruskal-Wallis tests and Spearman correlation, p <0.05. Results: We obtained data from 84 patients, 45 SpA (53.6%) and 39 (46.4%) RA patients. Table 1 presents the descriptive statistics of the continuous variables. In RA group, 92.3% were female, 84.6% under anti-TNF, 66.7% under their 1st biologic and we found an association between BMQ-SC score and HADS-anxiety (p=0.013) and positive correlations between BMQ-SC score and Patient Global Assessment (PGA) (p=0.031), VAS pain (p=0.004), Physician's Global Assessment (PhGA) (p=0.004), DAS28 (p=0.007), and HAQ (p <0.001). In SpA group, 62.2% were female, 86.7% under anti-TNF, 77.8% under their 1st biologic and BMQ-SN score was positively correlated with VAS nocturnal back pain (p=0.047), PhGA (p=0.045) and BASFI (p=0.003). Conclusion: In RA patients, those with higher disability and a clinically more active disease presented higher levels of concern regarding the medication. In SpA, patients with a more aggressive disease, with nocturnal pain and worse function have a stronger conviction of the necessity and efficacy of the medication. References: [1] Salgado T, Marques A, Geraldes L, Benrimoj S. Horne R. Fernandes-Llimos F. Cross-cultural adaptation of the Beliefs about Medicines Questionnaire into Portuguese. Sao Paulo Med J. 2013; 131(2):88-94. doi:10.1590/S1516-31802013000100018. Disclosure of Interests: Nathalie Madeira: None declared, Candida Silva: None declared, Claudia Miguel: None declared, Dina Medeiros: None declared, Filipe Barcelos Consultant for: Pfizer; Ely-Lilly, Speakers bureau: Novartis, Helena Santos: None declared, Ricardo Trinca: None declared, Alexandra Cardoso: None declared, Luís Cunha Miranda: None declared